Relationship of peripheral blood mononuclear cells miRNA expression and parasitic load in canine visceral Leishmaniasis - Bragato, Jaqueline Poleto [UNESP]; Melo, Larissa Martins [UNESP]; Venturin, Gabriela Lovizutto [UNESP]; Rebech, Gabriela Torres [UNESP]; Garcia, Leandro Encarnação [UNESP]; Lopes, Flavia Lombardi [UNESP]; de Lima, Valéria Marçal Felix [UNESP] (Public Library of Science (PLoS), 2018)
Visceral leishmaniasis (VL) in humans is a chronic and often fatal disease if left untreated. Dogs appear to be the main reservoir host for L. infantum infection, however, in many regions other canids such as jackals, foxes, wolves and other mammals, such as hares or black rats, have been implicated as wild reservoirs. Most dogs cannot form an effective immune response against this infection, and this could be modulated by small non-coding RNAs, called microRNAs, responsible for post-transcriptional control of gene expression. Here, we evaluated the expression of miRNAs in peripheral blood mononuclear cells (PBMC) of symptomatic dogs naturally infected with Leishmania (L.) infantum (n = 10) and compared to those of healthy dogs (n = 5). Microarray analysis revealed that miR-21, miR-424, miR-194 and miR-451 had a 3-fold increase in expression, miR-192, miR-503, and miR-371 had a 2-fold increase in expression, whereas a 2-fold reduction in expression was observed for miR-150 and miR-574. Real-time PCR validated the differential expression of miR-21, miR-150, miR-451, miR-192, miR-194, and miR-371. Parasite load of PBMC was measured by real-time PCR and correlated to the differentially expressed miRNAs, showing a strong positive correlation with expression of miR-194, a regular positive correlation with miR-371 expression, and a moderate negative correlation with miR-150 expression in PBMC. These findings suggest that Leishmania infection interferes with miRNAs expression in PBMC, and their correlation with parasite load may help in the identification of therapeutic targets in Canine Visceral Leishmaniasis (CVL).